Analisis Efektmtas Biaya Stimulus Fiskal Sektor Perhubungan (Studi Kasus Propinsi Sulawesi Selatan) - Siswanto, Adrianus Dwi (Warta Penelitian Perhubungan, 2010)
Infrastructure in the transport sector plm;s an important role in the dynamics of economic development.Infrastructure does not just praui.de support for the mobilihJ of goads and senlices but also thefirst to luwe an impact on employment creation as infrastructure projects are implemented. Thisstudy analyz.ed the effectiveness of job creation policies of fisazl stimulus in the conzmuniaztions sectar.17iis study uses the metlwdology Effectiuiness Cost Analysis (CEA), which describes how far thelevel of effectllx?ness of budget allocations that are m1ai.lnble to job creation directly. Furthermore, theexisting data obtained from indices tluzt portray the effecti'ueness of the budget/ cost required to createan emplm;ment. 11ie data used are secondnn; dntn.The suniei; results re-vealed that tlie project on the fiscal stimulus communications sector has arelatively law level of effectirieness. 17zis is shown by the indicators of financinl performance, andactual physical labor absorption is relntiziely inconsistent. 71ie percentage of emplm;ment is reflectedin tlie reiuization of tlze plan that tlie use of labor absorption is relnti1iely low compared to tlie realizationof financial and physical absorption. 71iis means that emplm;ment is expected for fiscal stimulusproject in South Sulawesi Province, is not commensurate with its financial absorption.Keywords: Infrastructure, Cost Analysis Effectiviness, tlie transportation sector, financial performance,plrysiazl performance and lnbor.